Correlated matrix‐assisted laser desorption/ionization mass spectrometry and fluorescent imaging of photocleavable peptide‐coded random bead‐arrays. (21st November 2013) - Lim, Mark J.; Liu, Ziying; Braunschweiger, Karen I.; Awad, Amany; Rothschild, Kenneth J.
<x xml:space="preserve">Abstract</x> RATIONALE Rapidly performing global proteomic screens is an important goal in the post‐genomic era. Correlated matrix‐assisted laser desorption/ionization mass spectrometry (MALDI‐MS) and fluorescent imaging of photocleavable peptide‐coded random bead‐arrays was evaluated as a critical step in a new method for proteomic screening that combines many of the advantages of MS with fluorescence‐based microarrays. METHODS Small peptide‐coded model bead libraries containing up to 20 different bead species were constructed by attaching peptides to 30–34 µm diameter glass, agarose or TentaGel® beads using photocleavable biotin or a custom‐designed photocleavable linker. The peptide‐coded bead libraries were randomly arrayed into custom gold‐coated micro‐well plates with 45 µm diameter wells and subjected to fluorescence and MALDI mass spectrometric imaging (MALDI‐MSI). RESULTS Photocleavable mass‐tags from individual beads in these libraries were spatially localized as 65 µm spots using MALDI‐MSI with high sensitivity and mass resolution. Fluorescently tagged beads were identified and correlated with their matching photocleavable mass‐tags by comparing the fluorescence and MALDI‐MS images of the same bead‐array. Post‐translational modification of the peptide Kemptide was also detected on individual beads in a photocleavable peptide‐coded bead‐array by MALDI‐MSI alone, after exposure of the beads to protein kinase A (PKA). CONCLUSIONS Correlated MALDI‐MS and fluorescent imaging of photocleavable peptide‐coded random bead‐arrays can provide a basis for performing global proteomic screening. © 2013 The Authors. Rapid Communications in Mass Spectrometry published by John Wiley & Sons, Ltd.